PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM PEMBELAJARAN KENAMPAKAN ALAM DAN BUATAN DI DAERAHKU UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 3 SD INPRES OEPURA 2 - TKIKHAU, TANTI ELSI; Suban Hali, Antonius; Nawa , Netty E. A. (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to determine the improvement in the learning outcomes of third-grade students using the Project Based Learning model on the topic of natural and artificial phenomena in my area. This type of research is Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of several stages: planning, implementation, observation, and reflection. This research is located at SD Inpres Oepura 2, Jin Kenanga, Naikolan, Maulafa District, Kota Kupang, with the subjects of the study being all students of class 3A at SD Inpres Oepura 2, totaling 23 students. The data collection techniques used by the researcher are: observation techniques, learning outcome tests, and documentation. The results of the data analysis show that students' learning outcomes through the application of the Project Based Learning model have improved. This is evidenced by the average completion rate of third-grade students in cycle I, where the completion percentage was 43.47% (10 students completed) and in cycle II, the completion percentage was 100% (23 students completed). Another improvement observed was the students' activity in class, which was measured using the observation sheet prepared by the researcher. From the results of the above research, it can be concluded that the application of the Project Based Learning model can improve the learning outcomes of third-grade students at Oepura 2 Public Elementary School.